SEALING MASONRY UNITS WITH EXPANDED POLYSTYRENE FOAM (EPS) - Souza, Leandro Moreno De; Assis, Cleber Decarli de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Expanded polystyrene is a 100% recyclable material , such contributes to the reduction of environmental impacts , this contribution occurs preventing the misuse of wastes that are currently disposed of in landfills or dumps with no control , caused due to the large volume occupied and the difficulty of preventing spread by wind action, damage to the environment . Another aspect is the power consumption associated with the manufacturing process of expanded polystyrene ( Styrofoam ) in the case of recycling , it may be possible to reduce the input (electricity , fuel, etc.). Since several initial manufacturing steps of the raw material virgin can be eliminated. One must consider that the expanded polystyrene is obtained from petroleum , which is an exhaustible natural mineral resource , and recycling means better use of this energy source . Expanded polystyrene foam has many advantages not only in relation to environmental issues , as well : low thermal conductivity, low density, which varies between 10 and 30 kg.m- ³ , low water absorption , low weight , ease of handling , versatility , aging resistance , shock absorption. These characteristics lead to note that this is an innovative material for which have been discovered and developed more and more noble uses and whose application possibilities still seem far from being fully exploited , even after more than half a century of application.